Hubungan antara Preeklamsia Berat dan Kelahiran Prematur di RS Dr. Oen Surakarta Periode 2014-2015 - Saputra, Angga Nuralam; , dr. Supanji Raharja, Sp.OG (K) (2017)
Background: Preeclampsia is one of the three main cause of maternal mortality. Preeclamsia, based on the degree of severity, is classified into mild and severe preeclamsia. Severe preeclampsia causes maternal mortality and morbidity, it also leads to hypoperfusion in the uteroplacental circulation and placenta ischemia, which can lead to babies born prematurely. Objective: This study was conducted to determine the relationship between severe preeclampsia and the incidence of low birth weight in babies at Dr. Oen Hospital, Surakarta. Methods: This study was designed as an analytic observational study with a cross-sectional approach. The data is taken from 108 samples of pregnant women in Dr. Oen Hospital, Surakarta, taken with purposive sampling techniques. The data is analyzed using the chi-square test. Results: From 108 samples, 54 samples experienced severe preeclampsia and 54 samples did not experience severe preeclampsia. The proportion of preterm birth from mothers with severe preeclampsia was 13.1%. Statistical test results between severe preeclampsia and the incidence of preterm birth are p 0.001 and RP 4.5. Conclusion: There is a significant relationship between severe preeclampsia and premature at Dr. Oen Hospital, Surakarta. Mothers with severe preeclampsia are at of 4.5 times greater risk to give birth to premature babies.